im, the Pengetahuan Terkait Gizi dalam Upaya Meningkatkan Imunitas melalui Kebiasaan Makan selama Pandemi Covid-19 : Nutritional Knowledge in Improving Immunity through Healthy Eating Habits during the Covid-19 Pandemic - Sri Wahyuni; Sri Sumarmi; Fathrizqita Aghnia Raudhany; Trias Mahmudiono (Amerta Nutrition, 2023)
Background: The spread of COVID-19 in Indonesia has caused many deaths. One of the ways to deal with COVID-19 is to increase immunity. Youth is the majority population group in the world, meaning many can potentially be exposed to the coronavirus. Youth, including students, tend to be easily exposed to the coronavirus because they have bad eating habits (lack of protein, vitamin C, and vitamin A intake). Bad eating habits can occur due to a lack of knowledge related to nutrition, especially those related to efforts to increase immunity.  Objectives: To determine the relationship between nutrition-related knowledge to increase body immunity with eating food sources of protein, vitamin A, and vitamin C during the covid-19 pandemic in Airlangga University students. Methods: Descriptive quantitative method used a cross-sectional research design with a sample of Airlangga University students. The data was obtained using an online survey using the accidental sampling method. Furthermore, the researcher distributed online questionnaires in the form of google forms with the help of media such as pamphlets through social media. Then the data were analyzed using the Chi-square test. Results: Most of the respondents were students of the Faculty of Public Health, female, 21 years old, and living with their nuclear family at home during the Covid-19 pandemic, have good knowledge of nutrition to increase immunity (75%), except for factors which can reduce immunity. There is a significant positive relationship between knowledge and eating habits. Conclusions: There was a significant relationship between knowledge related to nutrition to increase immunity during the covid-19 pandemic through eating food sources of protein, vitamin A, and vitamin C.